Nitrogen Fixation in a Changing Arctic Ocean: An Overlooked Source of Nitrogen? - von Friesen, Lisa W.; Riemann, Lasse (Frontiers in Microbiology, 2020)
The Arctic Ocean plays a significant role in global carbon biogeochemistry. Since climate change is rapidly changing fundamental components of the Arctic, it is of local and global importance to understand and predict consequences for its carbon dynamics. Primary production in the Arctic Ocean is often, and increasingly, nitrogen-limited. It is therefore of critical interest that biological nitrogen fixation, a process where some bacteria and archaea termed diazotrophs convert nitrogen gas to bioavailable ammonia, has now been detected in the Arctic Ocean. Several studies report diverse and active diazotrophs on various temporal and spatial scales across the Arctic Ocean, but their ecology and biogeochemical impact remain poorly constrained, and nitrogen fixation is absent from models of primary production in the Arctic Ocean. The composition of diazotrophs appears distinct from other oceans - challenging paradigms of function and regulation of nitrogen fixation. There is evidence of both symbiotic cyanobacterial nitrogen fixation and heterotrophic diazotrophy, but the vast uncharted regions and sparse quantitative data hamper conclusive insights. Hence, it remains to be determined to what extent nitrogen fixation represents a hitherto overlooked source of new nitrogen to consider when predicting future productivity of the Arctic Ocean. Here, we discuss current knowledge on diazotroph distribution, composition and activity in pelagic and sea ice-associated environments of the Arctic Ocean. Based on this, we identify gaps and outline pertinent research questions in the context of a climate change-influenced Arctic Ocean - with the aim of guiding and encouraging future research.